2014
DOI: 10.1111/fwb.12364
|View full text |Cite
|
Sign up to set email alerts
|

Forest canopy cover determines invertebrate diversity and ecosystem process rates in depositional zones of headwater streams

Abstract: Summary Previous studies of the ecological linkages between forest and headwater streams have focussed primarily on patterns and processes in erosional habitats, typically riffles. Depositional zones trap large amounts of sediments and particulate organic matter, suggesting that they may be important for forest–stream linkages. We studied the invertebrate benthos and two key ecological processes, surface sediment reworking and leaf litter breakdown, in the depositional zones of streams bordered by contrastin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 60 publications
(85 reference statements)
1
18
0
Order By: Relevance
“…, De Nadai‐Monoury et al. ). Many of these studies also demonstrate significant effects on functional properties such as consumer growth, primary production and decomposition, yet relatively little is known about how top‐down and bottom‐up drivers influence fluxes of energy and materials in food webs, especially at the natural ecosystem scale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, De Nadai‐Monoury et al. ). Many of these studies also demonstrate significant effects on functional properties such as consumer growth, primary production and decomposition, yet relatively little is known about how top‐down and bottom‐up drivers influence fluxes of energy and materials in food webs, especially at the natural ecosystem scale.…”
Section: Introductionmentioning
confidence: 99%
“…There is substantial evidence that both pathways are important in structuring ecosystems (Leroux and Loreau 2015). Many seminal studies have been conducted in freshwater systems (reviewed by Taylor et al 2015), where investigators have documented significant effects of predatory or planktivorous fishes (Carpenter and Kitchell 1988, Power 1990, Flecker and Townsend 1994, nutrient enrichment (Schindler 1977, Hambright et al 2007, Davis et al 2010, and light availability (Hill et al 1995, Ask et al 2009, De FISH AND LIGHT EFFECTS ON FOOD WEBS Nadai-Monoury et al 2014). Many of these studies also demonstrate significant effects on functional properties such as consumer growth, primary production and decomposition, yet relatively little is known about how top-down and bottom-up drivers influence fluxes of energy and materials in food webs, especially at the natural ecosystem scale.…”
Section: Introductionmentioning
confidence: 99%
“…High cover of overhanging riparian vegetation can minimize solar radiation reaching the stream channel, which is thought to moderate swings in water temperature and promote species, such as E. armatus , that prefer well‐oxygenated cool water (Geddes et al , ; Rutherford et al , ; McCarthy et al , ). Moreover, riparian vegetation may directly influence stream detritivores that feed on the leaf litter and other allochthonous materials that fall into the stream (Gregory et al , ; Wallace et al , ; Nadaï‐Monoury et al , ), upon which Murray crayfish have been found to aggregate and forage (Starrs et al , ). Significantly, evidence is building that higher abundances of crayfish are more likely to be found in streams embedded within intact and mature forests (Furse and Wild, ; Usio, ; Chucholl and Schrimpf, ).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, in freshwaters, the bioturbation ability of only a few species or taxonomic groups, including tubificids, chironomids, and clams, has been investigated (Fisher et al, 1980;Matisoff & Xiaosong, 1998;Ciutat et al, 2005;Stief & de Beer, 2006;Lagauzère et al, 2009;Mermillod-Blondin et al, 2013;Majdi et al, 2014a). Yet, the recent work of De Nadaï- Monoury et al (2013Monoury et al ( , 2014 has provided a wider overview of bioturbator diversity in freshwater ecosystems. In our experiment, sediment reworking tended to increase over time in all treatments (Fig.…”
Section: Discussionmentioning
confidence: 99%